The Effect of Dislocation and Interface-Roughness Scattering on Electron Mobility in the MgZnO/ZnO Heterostructure - DongFeng Liu (Advances in Materials Science and Engineering)
In this work, the electron mobility in the MgZnO/ZnO heterostructure at room temperature is theoretically studied by considering interface roughness (IFR), dislocation (DIS), and polar optical phonon (POP) scattering. Analytical formulae are introduced to calculate the critical thickness and dislocation density in the barrier layer of MgZnO/ZnO heterostructures. The calculated critical thickness for the MgZnO/ZnO heterostructure is much smaller than that for the AlGaN/GaN heterostructure system. At room temperatures, POP scattering is found to be the most important scattering mechanism. On the other hand, the change of electron mobility limited by IFR as a function of the barrier thickness in the MgZnO layer is found to be quite different to that limited by DIS. High-density (>1013cm−2) 2DEG can be obtained in the MgZnO/ZnO interface by increasing the thickness and Mg composition in the MgZnO layer.